Media Persona and Parasocial Relations of K-Drama Viewers on Instagram - Yuyun Hamzah; Pahrul Idham Kaliky; Antasari Bandjar (International Journal of Science and Society, 2021)
This research is a qualitative descriptive study that aims to provide an overview of the interactions and parasocial relationships of k-drama audiences with the characters in The World of The Married drama as the impact of mass communication. And to find out the characteristics, factors that influence parasocial relationships and at what level these parasocial relationships are intertwined with the S.O.R (Stimulus, Organism, Response) theory as a framework of thought. Primary data collection was carried out through online interviews with a number of informants from the k-drama audience of The World of The Married who were taken randomly from Instagram accounts. The results of this study indicate that the interaction between the audience and k-drama. The World of The Married gives rise to parasocial relationships with the following three characteristics, empathy toward the performer, seeking companionship, and imagined friendship. Parasocial relationships that exist are influenced by factors of motivation, identification and similarity. Thus, in the concept of interaction and parasocial relationships, Korean drama audiences can be grouped at the level of entertainment social-value and intense-personal feeling.